Transformative Change and Measuring Success: Public-Private Partnerships in British Columbia, 2001-2005 - Cohn, Daniel (Revue Gouvernance / Governance Review)

(untitled) (Centre d’études en gouvernance de l’Université d’Ottawa, 2006)
Public-private partnerships can be understood to be instruments for meeting the obligations of the state (things that there has been a strong social consensus that the state ought to do) that are transformed so as to involve private property ownership as a key element in the operation of the instrument. The word partnership is important and not just a euphemism for hiding a privatization (at least it ought not to be). Partnership means a relationship based on common goals where both entities share benefits and contribute resources over the long-term for mutual advantage and out of a sense of commitment. In a design-build-finance-operate (DBFO) public-private partnership, the state agency sponsoring the development hires either a single company (or consortium of companies) to, as the term suggests, meet the full extent of its public obligation by determining how best to meet the obligation, designing and building the necessary infrastructure and then operating it. This paper looks at the development of three DBFO public-private partnerships in and around Vancouver, British Columbia, asking what the likelihood is that the public will benefit from decisions to employ this procurement model. When using a definition of benefit that is broader than simply saving money, it is possible that these projects can provide greater benefits than a traditional public procurement, although the managers of two of the projects will likely face greater difficulties in doing so than the managers of the third one.